2014
DOI: 10.1088/0953-8984/26/26/265004
|View full text |Cite
|
Sign up to set email alerts
|

A charge optimized many-body potential for titanium nitride (TiN)

Abstract: This work presents a new empirical, variable charge potential for TiN systems in the charge-optimized many-body potential framework. The potential parameters were determined by fitting them to experimental data for the enthalpy of formation, lattice parameters, and elastic constants of rocksalt structured TiN. The potential does a good job of describing the fundamental physical properties (defect formation and surface energies) of TiN relative to the predictions of first-principles calculations. This potential… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(14 citation statements)
references
References 81 publications
(92 reference statements)
0
14
0
Order By: Relevance
“…Thus, reduction of the mineral surface, and the gradual formation of metallic Fe clusters, cannot be directly explored by the methodology. To go beyond this level of calculation, we are developing a Charge‐Optimized Many‐Body potential [ Cheng et al , , and references therein] for the Fe–Si–O system. This approach uses variable point charges and allows for the formation of elemental metal and deviations from perfect stoichiometry.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, reduction of the mineral surface, and the gradual formation of metallic Fe clusters, cannot be directly explored by the methodology. To go beyond this level of calculation, we are developing a Charge‐Optimized Many‐Body potential [ Cheng et al , , and references therein] for the Fe–Si–O system. This approach uses variable point charges and allows for the formation of elemental metal and deviations from perfect stoichiometry.…”
Section: Discussionmentioning
confidence: 99%
“…In some of the most advanced charge equilibration schemes, such as the charge optimized many body (COMB) potentials 9 and the ReaxFF 10 force field, the atomic charges depend on the environment via some analytic functions. These potentials have been successfully applied to study materials and other condensed matter systems [11][12][13] . Nevertheless, the basic shortcoming of all standard FFs, namely that the optimal analytical functional form is unknown, still remain in these FFs.…”
Section: Introductionmentioning
confidence: 99%
“…Using a revised set of potentials (COMB3), the authors found the nonpolar (101̅0) ZnO surface to be the most stable, and the polar surface to have the largest cleavage energy, with a favorable comparison to earlier DFT work. We note, however, that the surface model (an ideal clean termination) employed to calculate the cleavage energies for the polar ZnO surfaces is inappropriate, because it necessitates electron transfer between the opposite polar surfaces as the stabilization mechanism for these ZnO polar surfaces, for which there is no experimental evidence , and calculations yield higher surface energies as compared to the ionic reconstruction. , This new generation of potentials has been also used in other systems including TiN, TiO 2 and Ti, Si/HfO 2 , and Cu/SiO 2 . Furthermore, methodologically close, reactive force fields (ReaxFF) potentials have been suggested to study multicomponent systems with applications to metal-based heterogeneous systems, such as Cu/ZnO .…”
Section: Introductionmentioning
confidence: 99%